Cross-Border Enforcement of Consumer Banking Law - Haryanto, Joni (West Science Law and Human Rights, 2024)
This literature review examines the ongoing challenges and advancements in consumer protection within international finance and arbitration. It highlights regulatory failures, particularly in the context of high-profile financial scandals, underscoring the necessity for more robust financial regulations. The review discusses the issues of cross-jurisdictional consumer protection, focusing on the implications of regulatory arbitrage and its detrimental effects on consumer rights in global contexts. Additionally, it addresses the role of online dispute resolution as a means to reduce barriers to justice in cross-border financial transactions. The importance of fairness and efficiency in consumer arbitration processes is emphasized, particularly in relation to emerging digital finance models. The review also explores the critical issues of transparency and potential bias in international financial dispute resolution. Furthermore, it underscores the urgent need for reforms in international commercial law to effectively protect consumers amid the complexities of globalization and evolving financial landscapes. This compilation of insights presents a comprehensive understanding of consumer protection in cross-border financial environments, illustrating the necessity for improved regulatory frameworks and dispute resolution mechanisms to safeguard consumer rights effectively.